VALIDITAS TRIASE DILIHAT DARI HUBUNGAN LEVEL TRIASE TERHADAP LENGTH OF STAY PASIEN Di IGD - Eva Marti (The Indonesian Journal of Health Science, 2017)
High level of activities in the Emergency Room requires certain patient sorting system. Role of the triage system in emergency service is to determine which patients who need urgent care the most. Patients’ lenght of stay in the Emergency Room can be used as one of the indicators to evaluate clinical urgency of the patients treated by triage. The study used quantitative method with crosssectional observational analytic design. The purpose of the study was to describe the correlation between the patients’ triage level and their length of stay in the Emergency Room. The researcher analyzed the medical records of the 374 patients admitted to  Emergency Room in the first and second week of August 2015 in order to find out their triage level and length of stay in the Emergency Room. Bivariate analysis, particularly the Sperman’s-Rho analysis, was used to describe the correlation between each triage category and the length of stay in the Emergency Room. Based on the bivariate analysis, it was found that p    0.00  (  0.05)  and the correlation coefficient was 0.327.  The conclusion was based on the statistical analysis, there was significant correlation between triage level and length of stay in the Emergency Room and the level of significance was 0.327.